Psychological Vulnerability among University Students (Journal Of Educational and Psychological Researches, 2026)
The research aims to explore psychological vulnerability among university students. The researcher developed a scale of 32 items to measure psychological vulnerability among 382 male and female students who were selected randomly from the University of Baghdad for the academic year (2024-2025). The results showed that the sample generally has a low level of psychological vulnerability, with a higher level among females and students in the humanities fields. The study also indicated that psychological vulnerability is influenced by an individual's fixed cognitive structures, rather than academic experience or academic level, which is related to several factors, such as self-esteem, optimism, social support, and self-efficacy.